Demonstration of Aeration: Assessment of Fish Growth and Survival at Field Condition - Debnath, Chandan; Sahoo, Lopamudra (Indian Journal of Hill Farming, 2018)
The study examined the effect of aeration on growth and production of Indian major carps in earthen ponds (each of 0.1 ha in size and 1.5-2 m water depth) for 6 months (May-October 2015). Total six ponds were used, of which, three were provided with aeration using fountain aerator and remaining three kept non-aerated and served as control. Catla (40%), rohu (30%) and mrigal (30%) were stocked (10,000 fingerlings/ha) into the ponds and mustard oil cake and rice bran was fed to them (2-3% of body weight). Aeration was provided daily twice (7-8 am and 5-6pm) for one hour during each time. The water quality and fish growth was assessed on monthly intervals which showed significant increase in DO, pH and total alkalinity level of water of the aerated pond. Ammonia was in safe limit and plankton production was higher through aeration. Growth (in terms of wet weight) was 4.3% higher at catla, 4.9% higher at rohu and 16% higher at mrigal in aerated pond in comparison with non-aerated pond. Survival was 8% higher, thus production was 17% higher in aerated pond when compared with non-aerated pond. Feed conversion ratio in aerated pond (2.8) was better than non-aerated pond (3.3). Thus, the study concluded that aeration could be a potential mean for further enhancement of the fish production of Tripura from current level for doubling farmers’ income and livelihood security.